Socio-demographic characteristics on land records management practices in Tanzania - Mogha, Huruma; Dulle, Frankwell; Benard, Ronald (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Land registry offices are faced with misplacement and misfiling of records caused by improper practices by registry staff. Purpose: This study examined the influence of socio-demographic characteristics on the extent of land records management practices in land registry offices in district councils in Tanzania. Method: Qualitative and quantitative approaches were used to complete data collection and data analysis. A purposive sampling was used to select 160 land registry staff and 19 key informants. Quantitative data were analyzed by using SPSS version 26, while the qualitative data was analyzed by using content analysis with the aid of ATLAS.ti software. Findings: The findings show that there is a low practice among land registry staff of district councils. Age has a positive influence on LRMP, while career and working experience have a negative influence on LRMP. Conclusion: Adequate consideration should be given to individuals' age, experience, and career to a higher level of practices of land records in land registry offices. Training programs for non-professionals such as surveys, cartographers, and evaluators should be conducted to enhance their skills and competence in LRMP.